HVDC Transmission System with Medium-Frequency Transformers - Adil, Mohammed (My University, 2009)
For voltage adaptation and galvanic isolation in High Voltage Direct Current (HVDC) converter stations, standard transformers operating at grid frequency are currently used. These devices tend to be very large and heavy, which is undesirable in many applications. Transformers where the magnetic parts operate at a frequency considerably higher than the grid frequency could offer many advantages. Smaller and lighter transformers and lower losses are among them. In this thesis, a future-oriented HVDC converter station using a medium frequency MF transformer is studied with special focus on the converter circuits. The converter size used in this work is 78MW (±75kVDC/11kVAC) and the main application is power transmission to and from offshore installations. The converter consists of a snubbered Voltage-Source Converter VSC and 2-phase by 3-phase cycloconverter connected by a MF transformer. The VSC is implemented using a single phase leg and the cycloconverter is implemented using fast thyristors. It is expected that the semiconductor losses of the power conversion system will be significantly reduced by the use of the proposed converter topology which permits soft switching of all semiconductor valves in all operating points without any auxiliary valve. The thesis evaluates the commercial potential of the proposed HVDC system. A general circuit design based on available preconditions is made first for the studied converter station, and then a comparison with an existing two-level HVDC-Light station with regard to semiconductor requirements and losses is performed for the same operating point. The total space occupied by the valve installations for both systems is also estimated. The comparison shows that the proposed system promises a considerable reduction in the number of semiconductor devices and, as a result, the total volume of the converter valves. However, the semiconductor losses increase slightly.
Keywords: Elkraftteknik; Electric power engineering